Stable nanocrystalline structure attainment and strength enhancement of Cu base alloy using bi-modal distributed tungsten dispersoids. Issue 3 (1st February 2022) - Roy, Debdas; Pal, Snehanshu; Tiwary, Chandra Sekhar; Gupta, Ashish Kumar; Babu, Pokula Narendra; Mitra, Rahul
ABSTRACT : In this study, an experimental and atomic-scale simulation-based investigation has been performed to investigate the possible stability of the nano-crystalline structure and thereby considerable strength at a higher temperature in the case of synthesised Cu alloy along with logical understanding. Dispersions of high melting BCC metal (1 at% W) in nanostructured Cu is achieved using conveniently scalable cryomilling followed by hot pressing (at 550 °C). The thermal stability (till 800 °C) of grain size in synthesised nano-crystalline Cu alloy has been examined through X-ray diffraction (XRD) and Transmission Electron Microscopy (TEM). The nano-sized W particles dispersed at the Cu matrix grain boundaries, restricting grain growth by Zener pinning even after annealing was carried out at 800 °C. The hot-pressed pellets of nanocrystalline Cu99 W1 alloy with a nearly uniform distribution of W particles have exhibited higher hardness than pure Cu and increased in strength and strain to failure up to 10% and 46%, respectively. The improvement in mechanical properties is further rationalised by the Molecular Dynamics (MD) based simulation findings.